Innovation Technologies Forming Taxable Statements by a Joint Activity without Creation of a Legal Entity - Dmytrenko, Alla; Lebedyk, Galina; Nadobko, Vitalii; Zygun, Alina (International Journal of Engineering and Technology, 2018)
The article focuses on the improvement of the management system at economic objects in the conditions of application of advanced information technologies. The peculiarities of accounting of joint activity in the case of existence of an agreement on joint activity without the creation of a legal entity are investigated. It is proposed to set up a computer program for the possibility of forming standard accounting reports and regulated reporting, which will allow to conduct a complete accounting of joint activities. Â Â Â Â